Nanotechnology based approaches for detection and delivery of microRNA in healthcare and crop protection - Vrantika Chaudhary; Sumit Jangra; Neelam R. Yadav (Journal of Nanobiotechnology, 2018)
Abstract Nanobiotechnology has the potential to revolutionize diverse sectors including medicine, agriculture, food, textile and pharmaceuticals. Disease diagnostics, therapeutics and crop protection strategies are fast emerging using nanomaterials preferably nanobiomaterials. It has potential for development of novel nanobiomolecules which offer several advantages over conventional treatment methods. RNA nanoparticles with many unique features are promising candidates in disease treatment. The miRNAs are involved in many biochemical and developmental pathways and their regulation in plants and animals. These appear to be a powerful tool for controlling various pathological diseases in human, plants and animals, however there are challenges associated with miRNA based nanotechnology. Several advancements made in the field of miRNA therapeutics make it an attractive approach, but a lot more has to be explored in nanotechnology assisted miRNA therapy. The miRNA based technologies can be employed for detection and combating crop diseases as well. Despite these potential advantages, nanobiotechnology applications in the agricultural sector are still in its infancy and have not yet made its mark in comparison with healthcare sector. The review provides a platform to discuss nature, role and use of miRNAs in nanobiotechnology applications.